Study on the Response of Staggered Floor Isolated Structures in Mountainous Areas under Three-Dimensional Earthquakes. (12th July 2022) - Cheng, Shishan; Yang, Jie; Liu, Dewen; Chen, Lihao; Wan, Feng; Yang, Fan; Liu, Yang
Abstract : As coal mines are susceptible to safety accidents due to earthquakes, the requirements for structures in coal mining areas such as fire control centers and hospitals are higher, so base isolated structures, including staggered isolated structures, adapted to mountainous terrain are used in mining areas. The staggered floor isolated structure is a kind of isolated structure in mountainous areas which developed from the base-isolated structure. The theoretical research on staggered isolated structures is relatively few, and the theoretical research lags behind the practical application of engineering. In this paper, three staggered floor isolated structures with different heights of staggered floors are established. The responses of structures under one-dimensional, two-dimensional, and three-dimensional earthquakes are analyzed by the finite element dynamic time-history analysis method. The structural torsion, interstory shear force, maximum axial force, and floor displacement of the structure are compared. Due to the asymmetric characteristics of the staggered floor isolated structure, the center of stiffness of the staggered floor isolated structure deviates from the center of mass, which produces not only horizontal vibration but also obvious torsional vibration. The input of earthquakes in different dimensions also makes a difference in the response of the structure. The location between the upper isolated layer and the first floor above the upper isolated layer is a weak point of the structure. The results obtained in this study are distinguished from traditional basic isolated structures, which supplements the theoretical research of the staggered isolated structure.